134 Clinical predictors of informative genetic testing in patients with Hypertrophic Cardiomyopathy (HCM). (May 2019) - Ghazal Asswad, Amjad; Naraen, Akriti; Fairbairn, Timothy; Modi, Simon; Shaw, Matthew; Somauroo, John; Stables, Rod; Todd, Derick; McKay, Victoria; Cooper, Rob
Abstract : Background: HCM is a disease characterised by otherwise unexplained hypertrophy of the myocardium, often as a result of a gene mutation. Phenotypic expression is estimated at 1 in 500 and genetic prevalence at 1 in 200. Genetic testing is used primarily to facilitate predictive testing in family members. Method: A retrospective analysis of 174 consecutive HCM patients undergoing diagnostic genetic testing at a tertiary referral service in Liverpool, UK (January 2014 – February 2019) was performed. Univariate and multivariate analysis was performed on pre-defined clinical characteristics. Left ventricular morphology was assessed using echocardiography and cardiac MRI. Morphology was categorised into five groups: reverse curve, sigmoid, apical, concentric and focal. Standard HCM panels were performed via Oxford and Royal Brompton genetic laboratories. Class 4 and 5 variants were deemed 'informative'. Results: 72/174 (41.4%) genetic tests were informative. Those with informative tests were younger, with a mean age of 48.9 (confidence interval (CI) 45.5–52.3). Those with uninformative results had a mean age of 54.6 (CI 52.1–57.1) There was a higher incidence of positive Family History (FH) for HCM or sudden cardiac death (SCD) (43.1% vs 20.6%, p=0.002) in those with informative tests. Reverse curve morphology of the septum was seen in 70.8% of informative tests. Multivariate analysis demonstrated that reverse curve morphology (Odds ratio (OR) 2.85, CI 1.45–5.57, p=0.002), FH of SCD/HCM (OR 2.18, CI 1.07–4.42, p=0.031) and younger age at time of testing (OR 0.97, CI 0.94–0.99, p=0.007) were predictive of an informative test. Univariate analysis demonstrated that maximum wall width, T wave inversion on ECG and non-sustained VT on ambulatory ECG were not predictive of an informative test (n=125). An informative test was seen in 75.0% (12/16) of patients with all 3 predictors of age<50, FH HCM/SCD and reverse curve morphology. If 2 of 3 factors were seen, the chance of an informative test fell to 63.8% (30/47), 1 factor=29.9% (23/77) and 0 factors=20.6% (7/34). Patients with reverse curve morphology had informative genetic tests in 54.3% of cases (51/94) regardless of age at presentation. Those with an informative test were more likely to have an ICD. Of the 72 informative results, 26 had an ICD implanted compared with 20/102 with uninformative results (36.1% vs 19.6%, p=0.022). Variants in MYBPC3 were the most frequent accounting for 39 of the 72 (54.2%). MYH7 accounted for 17 cases (23.6%), TNNI3 for 4 (5.6%), FLNC=3 (4.2%), GLA=2 (2.8%), ACTC1=2 (2.8%), TNNT2=2 (2.8%), MYL2=1 (1.4%), MYL3=1 (1.4%) and TPM1=1 (1.4%). Conclusion: Reverse curve morphology of the septum (OR 2.85, CI 1.45–5.57), FH of SCD or HCM (OR 2.18, CI 1.07–4.42) and younger age at testing (OR 0.97, CI 0.94–0.99), are predictors of informative genetic testing in HCM, especially when two or more of these variables occur simultaneously (Table 1 ). Conflict of Interest: None